2016
DOI: 10.18632/oncotarget.9865
|View full text |Cite
|
Sign up to set email alerts
|

Glaucarubinone sensitizes KB cells to paclitaxel by inhibiting ABC transporters via ROS-dependent and p53-mediated activation of apoptotic signaling pathways

Abstract: Multidrug resistance (MDR) is considered to be the major contributor to failure of chemotherapy in oral squamous cell carcinoma (SCC). This study was aimed to explore the effects and mechanisms of glaucarubinone (GLU), one of the major quassinoids from Simarouba glauca DC, in potentiating cytotoxicity of paclitaxel (PTX), an anticancer drug in KB cells. Our data showed that the administration of GLU pre-treatment significantly enhanced PTX anti-proliferative effect in ABCB1 over-expressing KB cells. The Rh 123… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 33 publications
(59 reference statements)
1
10
0
Order By: Relevance
“…Therefore, many ROS-inducing agents are currently used in clinical trials for different tumors [21, 23]. These agents could not only act as direct inhibitors of cancers, but also sensitize tumor cells to chemotherapies [24]. In this study, we evaluated the growth inhibition and apoptosis induction by juglone in human GBM TSCs in vitro and in vivo, and we also confirmed that ROS was involved in juglone-induced apoptosis.…”
Section: Discussionsupporting
confidence: 56%
“…Therefore, many ROS-inducing agents are currently used in clinical trials for different tumors [21, 23]. These agents could not only act as direct inhibitors of cancers, but also sensitize tumor cells to chemotherapies [24]. In this study, we evaluated the growth inhibition and apoptosis induction by juglone in human GBM TSCs in vitro and in vivo, and we also confirmed that ROS was involved in juglone-induced apoptosis.…”
Section: Discussionsupporting
confidence: 56%
“…knockdown increased the expression of the human equilibrative nucleoside transporter 1 (hENT1), which is responsible for cellular gemcitabine uptake (158). This sensitisation may not be gemcitabine chemotherapy specific and glaucarubinone treatment and more specifically, PAK inhibition, may result in sensitisation of chemotherapy as suggested by a study where glaucaurbinone sensitised oral squamous cell carcinoma to the chemotherapy, paclitaxel (107).…”
Section: Discussionmentioning
confidence: 99%
“…Induction of apoptosis is recognized as a major anticancer mechanism for many chemotherapeutic agents, including the currently studied CYT‐Rx20 . Previous studies reported that the caspase family mediated apoptotic programmed cell death in oral cancer . Caspase‐9 is activated very early in the apoptotic cascade by cytochrome C, which is released from the mitochondria in response to apoptotic stimuli, and then downstream caspases, such as caspase‐3, are activated leading to the cleavage of key cellular proteins, such as PARP.…”
Section: Discussionmentioning
confidence: 99%